The Influence of Health Education on Mom's Knowledge and Attitude About Infant Massage - Andria Andria; Sri Wulandari; Eka Yulia Handayani; Ratih Ayuningtiyas; Isna Ovari (International Journal on Advanced Science, Education, and Religion, 2021)
Baby massage is an activity to simulate or sequence the baby's head with touch, movement, plus auditory stimulation and visual stimulation. The benefits of baby massage can make babies relax, establish affection between parents and children, and also train children's motor skills. Babies who routinely undergo baby massage are proven to have more motor intelligence than babies who rarely get it. The purpose of this study was to determine the effect of health education on mothers' knowledge and attitudes about infant massage in Pasir Makmur Village, Rambah Samo District, Rokan Hulu Regency. This type of research is a quasi experiment with a one group pretest posttest without control design. The number of samples is 65 people who are determined by total sampling technique. The statistical test used is the paired t test. The results showed that the average knowledge of respondents before being given health education about baby massage was 68.76 and after being given health education it was 88.18. The attitude of the respondents before being given health education on average was 42.04 and after being given health education it became 45.48. Based on the results of statistical tests there is an effect of health education on mother's knowledge and attitudes about infant massage with statistical test results obtained p values ​​are 0.0003 and 0.0002 (p <0.05). It is hoped that further research will not only provide health education but baby massage training so that mothers do not only massage their babies but can also be an effort for mothers to obtain a lot of material. Keywords: Health Education, Baby Massage, Infant Message